Application of nanotechnology in oil well cementing – an overview of the challenges associated with well cementing in difficult conditions - А.Y. Abusal Yousef; Ali I. Mohammedameen; Rustem А. Ismakov; Elmira D. Muftakhova; Artur R. Yahin (Нанотехнологии в строительстве)
Introduction. Nanotechnology has received a lot of attention in the oil and gas industry as an effective means of improving properties and increasing production rates, especially in harsh environments such as ultra-deep and shallow gas fields, deviated and horizontal wells, geothermal zones, and high pressure/high temperature (HPHT) areas. These environments present numerous economic, technical, operational, and HSE challenges that need to be addressed.Cementing operations play a critical role in these environments, as the cement sheath serves as a barrier to meet the different well conditions, including pressure, temperature, and the flow of liquids or gases. The use of nanomaterials as additives to cement has been credited with improving its properties and performance under these complicated conditions. Methods and materials. The study presents an analysis of the effect of pressure and temperature on the behavior and complexity of cementing operations in high-pressure wells. Analytical performance of the main characteristics of nanoclay (structural and mechanical) and evaluation of its effect on the durability and strength of cement slurry during well construction are presented. Results and Discussion. The results of the study allow us to conclude that nanoclay can be widely used as an additive to improve the durability and properties of cement-based materials under difficult conditions. Conclusions. The results of this study provide valuable information to researchers, engineers and practitioners in the field of cementing oil and gas wells, especially in solving problems related to providing the most favorable conditions for well operation with the long-term use of more durable cement slurry